Analisis Kinerja Keuangan RSUD Simpang Lima Gumul Sebelum dan Sesudah Penerapan PPK-BLUD - Anneke Shierly Frycillia Widodo; Erna Puspita; Sigit Puji Winarko (Perspektif Akuntansi, 2022)
PPK-BLUD is one of system which give flexibility for SKPD to build and opeate bussiness practice and still have a priority to increase a service quality for public. One of the goals of the estabilishment of a PPK-BLUD is to realize a prosperous society. BLUD status widely applied in the health service environment such as health center or general hospital. One of the hosptal which applied a BLUD system is RSUD SLG Kediri. RSUD SLG is under the aupspices of the Kediri District Health Office. This research have an purpose to analyze financial performance of RSUD SLG Kediri before and after applied PPK-BLUD. The variabel used in this research is some of financial ratio such as profitability ratio, liquidity ratio and solvability ratio.The analysis technique used is Paired Sample T Test. The statistical result show that Asymp sig is 0,010 or less than 0,05. So it can be conclude that there are different on financial performe of RSUD SLG before and after applied PPK- BLUD